PENGOLAHAN LIMBAH DOMBA MENJADI BOKASHI DI DESA ARJOWILANGUN, KECAMATAN KALIPARE KABUPATEN MALANG - Choiron, Moch Agus; Azizah, Siti; Hidayati, Nafisah Arina (DIKEMAS (Jurnal Pengabdian Kepada Masyarakat), 2020)
Arjowilangun Village is a post-TKI village. People choose to become sheep farmers with less capital than being cattle farmers. Based on the previous discussion, waste management is required to ensure the sustainability of environment in Arjowilangun Village. Processing sheep and agricultural waste program is held by Doktor Mengabdi team. Farmers can learn how to make Bokashi from waste. The method used is composting aerobic or anaerobic starters for composting organic material. A decomposer as collection of several good microbes from fungi work to control pathogenic microbes assists the fermentation process. Based on the results of the pre-test and post-test during the training, it can be showed that understanding of the breeders' potential of the environment is increased.